2012
DOI: 10.1016/j.ijnurstu.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding clinical risk decision making regarding development of depression during interferon-alpha treatment for hepatitis-C: A qualitative interview study

Abstract: Background: Hepatitis C virus (HCV) affects 170 million worldwide. Currently, around 30%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…We also highlight some studies we present in this section that show the differences between the actions of experienced and inexperienced workers as potential object for analysis in order to enable the design of suitable tools for supporting patient triage [31,32]. Understanding human performance and context variables involved in transferring information from junior staff to senior staff—and, eventually, to nursing staff—is an essential aspect in designing work processes in patient triage, as deficiencies in this process may occur because of not only lack of experience but also unavailability of information about patient conditions, poor risk assessment guidelines, communication failures, and lack of consideration to the human, technical, and patient factors involved in this critical process.…”
Section: Resultsmentioning
confidence: 99%
“…We also highlight some studies we present in this section that show the differences between the actions of experienced and inexperienced workers as potential object for analysis in order to enable the design of suitable tools for supporting patient triage [31,32]. Understanding human performance and context variables involved in transferring information from junior staff to senior staff—and, eventually, to nursing staff—is an essential aspect in designing work processes in patient triage, as deficiencies in this process may occur because of not only lack of experience but also unavailability of information about patient conditions, poor risk assessment guidelines, communication failures, and lack of consideration to the human, technical, and patient factors involved in this critical process.…”
Section: Resultsmentioning
confidence: 99%
“…There are 4 genotypes (HEV1-HEV4) that are part of a single serotype. 42 HEV1 and HEV2 are found only in humans, with the main transmission being fecal-oral route from contaminated water. HEV3 and HEV4 can infect humans, pigs, and other mammals.…”
Section: Hevmentioning
confidence: 99%
“…Previous studies have indicated that most hepatitis C patients have low socioeconomic backgrounds, which could explain why they have more oral health problems compared with healthy people (Coates et al, 2000;Hayashi et al, 2013;Jane, Chiu, Chen, Lin, & Chen, 2016) and this, in turn, increases their tendency to drop out of the AVT, which lasts for 24-48 weeks (Hepgul et al, 2012;Nagao et al, 2012;Saito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%